A comparison of fire safety management between public and private universities residential colleges / Mohd Hazri Md Yunus - Md Yunus, Mohd Hazri (Faculty of Architecture, Planning and Surveying, 2013)
The preparation of this dissertation is mainly motivated by the desire to provide an overview of the fire safety management and the level of awareness for fire safety among the occupant at private and public universities residential colleges. This intended to establish the good practise for adopted in the event of any emergency situation. This study has specific aims and objectives to achieve in the end of the research. The primary aim of this research is to study the fire safety management implemented in public universities residential colleges. In order to achieve that, there are several objectives need to be determined, to study the fire safety management in public and private universities residential colleges, to compare the management of fire safety at public and private universities residential colleges and to find out the resident satisfactions on fire safety management. This dissertation is divided into six chapters that cover the development of the study from the background investigations and researches to the final conclusions and recommendations. This dissertation includes the outline of introduction to the subject, background and objectives of the research. The problem statements, limitation of research and scope of research are also explained in chapter one. there are several type of methodology had been used of this study. This methodology process carried out based on literature review, interview observation, primary data and secondary data, and also includes questionnaire survey. The data collection based on questioner survey will be analyzed using statistical method and it following with conclusions and recommendations.